Characterization of hysteresis free, low-temperature hydrothermally synthesized zinc oxide for enhanced humidity sensing - Riza, Muhammad Arif; Go, Yun Ii; Maier, Robert R. J.; Harun, Sulaiman Wadi; Ahmad Anas, Siti Barirah (KeAi Publishing, 2021)
The hygroscopic properties of a material allow water retention and release of water vapor from surface of a nanostructure. Most nanostructure exhibit morphological change due to swelling or directional expansion upon water intake. The study focuses on characterizing the hygroscopic properties of additive enhanced zinc oxide via weighing method and testing of its hysteresis free sensing potential. Zinc oxide (ZnO) was prepared along with added additive via modified low temperature hydrothermal synthesis. The growth solution was coated on to glass slides before characterization of hygroscopicity and water adsorption hysteresis. The sample was placed in a sealed chamber with sensitive microbalance to measure mass gain and loss of the sample. The humidity within the chamber was manipulated chemically and temperature was left at constant ambient temperature. Relative humidity range from 40 to 80 % RH was exposed to the samples. The additive enhanced zinc oxide (ZnO-HMT) film has shown superior water retention and release capabilities by having steeper gradient compared to its initial version. ZnO-HMT could maintain its mass at low RH% of 37.5 % and high RH% of 80 % at closely similar value upon exposed to several cycles of incremental and decremental RH%. The mass intake and release of ZnO-HMT was also greater at 1.5 mg per 10 % increment and decrement of RH within 40 RH% - 80 RH% compared to ZnO which only have 0.9 mg mass change at each increment. Microscopic observation has shown apparent morphology change to ZnO-HMT nanostructure upon exposed to increased humidity from lower humidity. ZnO-HMT shown potent candidate as a humidity sensor material to be implemented into optical sensors that requires strain as the sensing mechanism to take advantage of the hygroscopic nature of the material.